Increasing the energy efficiency of auxiliary machines of AC electric locomotive - Yu. M. Kulinich; S. A. Shukharev; A. V. Gulyaev (Вестник Научно-исследовательского института железнодорожного транспорта)
Currently, an asynchronous variable frequency drive based on semiconductor converters is widely used due to the relative simplicity and reliability of the design. The use of digital microprocessor systems ensures high accuracy and flexibility of drive control. On the domestic rolling stock, the widespread introduction of asynchronous motors began to replace DC traction motors with sequential excitation. In particular, scalar-controlled asynchronous motors are used on serially produced 2TE25A diesel locomotives and EP20 electric locomotives. The auxiliary asynchronous machines of these locomotives are controlled by the vector control method. The use of a new type of engine on the rolling stock makes it possible to achieve a significant increase in the quality of consumed energy and reduce the consumption of electricity for traction of trains. Ensuring the energy efficiency of the drive in a wide range of loads requires further research. In this regard, the issue of saving energy resources becomes very urgent. The article proposes a vector control scheme for asynchronous motors of auxiliary machines of an electric locomotive, which implements an extreme method of control according to the criterion of minimizing the consumed current. The analysis of the engine operation is carried out based on its mathematical model in a rotating coordinate system d — q, which is implemented in the MatLab/Simulink software package. As a result of simulation modeling, it was found that the extreme control system with a variable step allows for each fixed value of the electromagnetic moment of the motor in the minimum time to find the optimal (extreme) value of the magnetic flux of the motor rotor, which corresponds to the minimum value of the stator current. The developed model of the motor with vector control is supplemented with an extreme regulator device, which allows achieving the best energy performance of the motor and reducing electrical losses in all operating modes with a minimum search time. The presented research results can be used in the development of energy-saving control systems for an asynchronous motor.